Comparison of Goniometry Method with Tape Method to Measure Trunk Mobility - Purvi Patel; Neha Mukkamala (Challenges and Advances in Pharmaceutical Research Vol. 2, 2022)
Tape method is most commonly used and is considered as the standard and most commonly used method for measuring spine mobility. The goniometric method, although not the most accurate, seems to be clinically accessible, objective and easy to use of measuring spinal mobility but not many studies have used and tested it for measuring spine ROM in healthy subjects. The chapter consists of discussion on specific, sensitivity and accuracy of goniometer compared with tape method for measuring spinal mobility in all planes (sagittal, frontal and transverse) in healthy adults. it also recommends method which can be used for measuring each movement of spine with their possible reasons.